2019
DOI: 10.1167/iovs.18-24908
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Spatial Hearing in Amblyopia: Evidence for Calibration of Auditory Maps by Retinocollicular Input in Humans

Abstract: PURPOSE. Evidence from animals and blind humans suggests that early visual experience influences the developmental calibration of auditory localization. Hypothesizing that unilateral amblyopia may involve cross-modal deficits in spatial hearing, we measured the precision and accuracy of sound localization in humans with amblyopia. METHODS. All participants passed a standard hearing test. Experiment 1 measured sound localization precision for click stimuli in 10 adults with amblyopia and 10 controls using a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…A few studies have investigated multisensory processing after visual sensory deprivation (see also Richards et al., 2019b for a review; Röder and Kekunnaya, 2021 for a review). Animal studies have shown that whereas the number of multisensory neurons in cats that were raised in complete darkness does not differ from sighted control animals, the response properties of those neurons differed between dark-reared and sighted control cats ( Wallace et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated multisensory processing after visual sensory deprivation (see also Richards et al., 2019b for a review; Röder and Kekunnaya, 2021 for a review). Animal studies have shown that whereas the number of multisensory neurons in cats that were raised in complete darkness does not differ from sighted control animals, the response properties of those neurons differed between dark-reared and sighted control cats ( Wallace et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%